Aven Green music machine - Bowling, Dusti (Aven Green, 2022)
Eight-year-old Aven Green is despondent when she does not master the piano in one day, but with new inspiration from guitarist Mr. Tom, who is armless like her, along with a special gift from her great-grandma, Aven learns she does not need to be perfect to perform.